2012
DOI: 10.1002/ana.23749
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the immunoglobulin heavy chain locus are associated with the IgG index in multiple sclerosis

Abstract: Objective Intrathecal synthesis of immunoglobulin gamma (IgG) synthesis is frequently observed in patients with multiple sclerosis (MS). Whereas the extent of intrathecal IgG synthesis varies largely between patients, it remains rather constant in the individual patient over time. The aim of this study was to identify common genetic variants associated with the IgG index as a marker of intrathecal IgG synthesis in MS. Methods We performed a genome-wide association study of the IgG index in a discovery series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 43 publications
7
38
5
Order By: Relevance
“…In this work, we investigate the association with MS of single nucleotide polymorphisms (SNPs) within the IGHC locus and their relationship with the intrathecal IgG and IgM synthesis, as well as with the presence of OCBs for both Igs. In addition to confirming the findings of Buck et al 14 regarding the association of the IGHC locus with the IgG index, we observed that the selected variant was associated with both MS susceptibility and IgM status.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this work, we investigate the association with MS of single nucleotide polymorphisms (SNPs) within the IGHC locus and their relationship with the intrathecal IgG and IgM synthesis, as well as with the presence of OCBs for both Igs. In addition to confirming the findings of Buck et al 14 regarding the association of the IGHC locus with the IgG index, we observed that the selected variant was associated with both MS susceptibility and IgM status.…”
Section: Introductionsupporting
confidence: 91%
“…SNP selection and genotyping SNP selection was based on the SNPs described by Buck et al 14 to the manufacturer's specifications. Genotyping call rates were >95% in each cohort analysed and 10% of the samples were genotyped in duplicate with >99% concordance.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic markers of the IgG heavy chain genes known to be determinants of Gm allotype polymorphisms have recently been shown to be associated with intrathecal levels of IgG,5, 6, 7 age at onset,6 and disease risk 7. The intrathecal humoral immune response in MS is dominated by the IgG1 subclass,8 and an early study showed an increased G1m1 to G1m3 ratio of IgG1 in the CSF of G1m1/G1m3 heterozygous MS patients 9.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that genetic variants in the IGHG1 gene on chromosome 14 coding for the G1m allotypes on the IgG1 constant chain influence IgG levels in the CSF and MS risk 9, 10, 11. We recently demonstrated a dominance of plasmablasts carrying the G1m1 allotype in the CSF of G1m1/G1m3 heterozygous MS patients, as opposed to patients with neuroborreliosis 12.…”
Section: Introductionmentioning
confidence: 91%